Net zero energy design : a guide for commercial architecture - Hootman, Tom. (Hoboken, New Jersey : John Wiley & Son, Inc., 2013)
Conveniently organized and packed with robust technical content and clear explanations of key principles Written by an architect who is the director of sustainability at a global architecture firm, Net Zero Energy Design is a practical guide for architects and related construction professionals who want to design and build net zero energy commercial architecture. It offers no-nonsense strategies, step-by-step technical analysis, and valuable examples, in addition to developed case studies. With a focus on application in a variety of building types and scales, the book also develops a broad-based understanding of all the integrated principles involved in achieving net zero energy. This book is an indispensable resource for anyone venturing into net zero energy design, construction, and operation, and it also serves as an excellent resource on a variety of sustainable design topics. Important features include: Organization based upon the commercial building delivery process Robust technical content for use in actual project applications Analysis examples that demonstrate key technical principles Plenty of design data for use as a valuable design resource Abundant and sophisticated information graphics and color illustrations and photographs A distinct design focus on the content that inspires adoption of principles into projects
Introduction -- 1. Net zero energy buildings -- 2. Project conception and delivery -- 3. Integrated process -- 4. Energy -- 5. Design fundamentals -- 6. Passive architecture -- 7. Energy-efficient building systems -- 8. Renewable energy -- 9. Economics -- 10. Operations and occupancy -- 11. Net zero energy -- 12. Case studies: DOE/NREL research support facility -- Bibliography -- About the author -- Index.
Includes bibliographical references and index.
Keywords: COMMERCIAL BUILDINGS -- ENERGY CONSERVATION